Procedural Controls Associated with OSH Culture among Heavy Equipment and Lifting Workers at PT XYZ, Balikpapan - Yifrans Sastra Wiguna; Anis Rohmana Malik; Aulia Rahma (G-Tech: Jurnal Teknologi Terapan, 2026)
Occupational safety and health (OSH) culture is essential in heavy-equipment and lifting services because safe performance depends on consistent procedural control, communication, and worker participation. This study examined factors associated with OSH culture among all 55 active workers of PT XYZ, representing operational units involved in transportation, lifting, and heavy-equipment services in PT XYZ. A quantitative cross-sectional design was applied using a structured four-point Likert-scale questionnaire. Data were analyzed through descriptive statistics, chi-square tests, and exploratory logistic regression. Overall, 63.6% of workers were categorized as having a good OSH culture. Age, gender, education level, and work tenure were not significantly associated with OSH culture, whereas work unit, worker involvement, OSH knowledge, PPE compliance, management commitment, OSH rules and procedures, leadership, teamwork, and work environment showed significant bivariate associations. In the final regression model, OSH rules and procedures showed the strongest association with good OSH culture (p < 0.001; OR = 136.00; 95% CI = 14.05–1,315.98). Because the model showed sparse-data instability, this result is interpreted as an exploratory association rather than causal proof. The findings support procedural strengthening through SOP monitoring, practical lifting training, direct supervision, discipline, and standardized crane communication.